Regenerative Tourism in the Philippines: Millennial Tourists’ Perspective and Intent to Participate - Lalisan, April Kim; Rahayu, Karisma Sri; Ating, Rashid; Gesmundo, Aefre; Samrach , Meta; Ork, Sereirath; Gersalia, Rommel (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
Tourism development can put destinations on a more equitable and environmentally friendly path by applying regenerative principles to tourism development. The millennial generation, known as sustainability-conscious consumers, bears much potential to participate in regenerative tourism. This study aimed to determine the awareness, perceived value, and intent to participate in regenerative tourism of the millennial generation in the Philippines in Metropolitan Manila and the surrounding areas such as Bulacan, Cavite, Angeles City, Cavite, Laguna, and others. This type of research is explanatory research, conducted through direct surveys of 190 millennial Filipinos through online questionnaires. Data was analyzed using SEM-PLS. The results of this study provide insights into the readiness of the millennial generation to participate in regenerative tourism practices. This research intends to contribute theoretically to tourism readiness and recovery post-pandemic. Moreover, it can make a practical contribution to tourism stakeholders to support the regenerative and sustainable development of tourist destinations in the Philippines.